Ethnobotanical Characteristics of The Millet Plant Along the Lower Amudarya (Eurasian Research Bulletin, 2023)
Distribution of the millet plant in the lower part of the Amudarya and its ethnobotanical features, millet juice is one of the main nutrients of the Karakalpak people.’’Maysok’’ prepared from it is considered a wedding and festive dish, not just a calorie-dense food